Beyond the COVID-19 crisis: building on lost opportunities in the history of public health - Jones, Esyllt; MacDougall, Heather; Monnais, Laurence; Hanley, James; Carstairs, Catherine (Facets, 2021)
The influenza pandemic of 1918–1920, which killed 50 000 Canadians, spurred the creation of a federal department of public health. But in the intervening century, public health at all levels has remained, as Marc Lalonde put it in 1988, the “poor cousin” in the health care system (Lalonde 1988, p. 77). Punctuated by sporadic investment during infectious disease crises, such as polio in the early 1950s, public health is less of a priority as the cost of tertiary health interventions rises. While public health potentially involves a broad range of interventions, this paper focuses on the history of public health interventions around infectious disease. COVID-19 has forced us to relearn the importance of maintaining basic infectious/communicable disease control capacity and revealed the cost of our failure to do so. It has also drawn our attention to the intersection between social inequality, racism, and colonialism and vulnerability to disease. In addition to investing in our capacity to contain disease outbreaks as they occur, we must plan now for how to achieve greater health equity in the future by addressing underlying economic and social conditions and providing meaningful access to preventive care for all. This is how we build a truly resilient society. Governments at all levels have recognized the importance of social factors in shaping health and illness for decades. But greater health equity will result only from genuine action on this knowledge. Action will arise from public advocacy in support of prevention, and a new level of engagement and collaboration between affected individuals and communities, public health experts, and governments.
Keywords: =CL